Innocent or guilty? a case of diverticular appendix - Rouxinol, Margarida Pires; Batista, Maria Gualter; Marques, Carolina; Silva, Sílvia; Silva, André; Ribeiro, Artur; Vieira Sousa, Paulo Jorge; de Sousa, João Pinto (International Surgery Journal, 2025)
Appendix diverticulosis is a relatively rare pathological finding, more common in adult men over the age of 60 years. It is generally an incidental finding on computed tomography (CT) and is clinically asymptomatic. When symptomatic, it is generally complicated by acute or chronic diverticulitis, with or without acute appendicitis. Appendix diverticulosis may be associated with appendix tumors, particularly mucinous ones. The article reports a clinical case of a 68-year-old man referred to a general surgery consultation due to densification of retrocecal fat with associated adenopathies, in the context of investigating abdominal pain. Prophylactic appendectomy is the recommended treatment given the potential for inflammation, perforation and the risk of developing tumors.